Engineered hybrid cell membrane nanosystems for treating cardiovascular diseases - He Lu; Yaohui Jiang; Rui Luo; Dexing Zhou; Feihu Zheng; Liran Shi; He Zhang; Yong Wang; Xiaodong Xu; Renfang Zou; Yujing Zhou; Shuai Ren; et al. (Materials Today Bio, 2025)
Cardiovascular diseases (CVDs) continue to represent a major challenge to global health, highlighting the urgent need for innovative treatment approaches. As a growing interdisciplinary field, nanotechnology has demonstrated significant potential for clinical applications. Nanomedicine development primarily focuses on improving the disease diagnosis and treatment through leveraging the distinct characteristics of engineered nanoparticles (NPs) to detect disease markers or deliver therapeutics to specific targets. Specifically, cell membrane-coated NPs offer enhanced targeting, biostability, and immune evasion. A significant benefit associated with this technology lies in its capacity to retain the functional and intrinsic properties of the source cells. However, while each cell membrane possesses distinct characteristics, a single cell membrane may not always address complex functional requirements. By combining membranes from different cell types, it becomes possible to integrate diverse functionalities, resulting in a more comprehensive solution. In this review, we aim to explore recent advancements in the hybrid cell membrane-coated NPs (HM/NPs) and their potential applications for the treatment of CVDs. We highlight the mechanisms underlying HM/NPs and their utilization in the therapeutic management of CVDs. Additionally, we examine the potential for clinical translation and discuss the key challenges encountered in this process.